2010
DOI: 10.4321/s1130-14732010000400004
|View full text |Cite
|
Sign up to set email alerts
|

Resección de tumor intramedular guiada por fluorescencia con ácido aminolevulínico

Abstract: ResumenLa resección guiada por fluorescencia con ácido aminolevulínico (5-ALA) se ha demostrado útil para el tratamiento quirúrgico de los gliomas cerebrales malignos. También parece útil en el tratamiento de otros tipos de tumores, tanto cerebrales como intramedulares. Presentamos el caso de un paciente con un tumor intramedular en el que la fluorescencia con 5-ALA fue de utilidad para la localización intraoperatoria de la lesión, para la identificación de pequeños nódulos en el parénquima medular y para logr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…5-ALA is a useful tool to treat malignant brain gliomas as well as other tumors. The usefulness of 5-ALA in ependymomas already has been reported in the literature [5,7,9,12-14]. Our results showed that 5-ALA helps to identify the dissection plane between normal tissue and the tumor.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…5-ALA is a useful tool to treat malignant brain gliomas as well as other tumors. The usefulness of 5-ALA in ependymomas already has been reported in the literature [5,7,9,12-14]. Our results showed that 5-ALA helps to identify the dissection plane between normal tissue and the tumor.…”
Section: Discussionsupporting
confidence: 73%
“…Deterioration of sensory function is inevitable due to the myelotomy, and studies have shown a correlation between the length of the myelotomy and postoperative sensory deficit [29,30]. As we reported previously [9], 5-ALA can help to locate the point to perform the myelotomy as well as to determine its length, which, in turn, may lead to a minor sensory function deficit (Fig. 2).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…It has been described that 5-ALA fluorescence helps to visualize tumor tissue in real-time during surgery, and most of the studies have been performed using fluorescence microscopy [1013] or, much less frequently, an endoscope [14]. Both neurosurgical microscopes and neuroendoscopes may be modified to detect 5-ALA-induced fluorescence.…”
Section: Introductionmentioning
confidence: 99%